2012
DOI: 10.1186/2251-6581-11-12
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and associated factors in recent-onset type 1 diabetic children in Iran

Abstract: BackgroundIn this study, the prevalence of vitamin D deficiency was assessed in a group of children and adolescent patients with recent-onset type 1 diabetes mellitus (T1DM).MethodsFifty-three patients with age 8–18 years and duration of T1DM less than 8 weeks were recruited. A food frequency questionnaire (FFQ) was used to assess dietary vitamin D and calcium intake. Sunshine exposure was measured using a questionnaire to quantify the amount of time children spent in the sun and other sun-related habits, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
6
7
0
2
Order By: Relevance
“…These findings have been recorded repeatedly in various studies,7 8 27 indicating that there could be a relationship between greater pigmentation and a less than ideal vitamin D status. Production of vitamin D precursors from exposure to UV radiation is inversely correlated with skin melanin density 28…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…These findings have been recorded repeatedly in various studies,7 8 27 indicating that there could be a relationship between greater pigmentation and a less than ideal vitamin D status. Production of vitamin D precursors from exposure to UV radiation is inversely correlated with skin melanin density 28…”
Section: Discussionmentioning
confidence: 63%
“…The prevalence of vitamin D deficiency was also shown to be higher among Malaysian adolescents of Indian and Malay ethnicity compared with the Chinese. These findings have been recorded repeatedly in various studies, 7 8 27 indicating that there could be a relationship between greater pigmentation and a less than ideal vitamin D status. Production of vitamin D precursors from exposure to UV radiation is inversely correlated with skin melanin density.…”
Section: Discussionmentioning
confidence: 63%
“…A study of 170 T1DM patients and 170 age, gender and ethnicity matched controls (age >16 years) revealed that vitamin D deficiency was considerably higher in T1DM children (90.6%) compared to controls (85.3%) (72). Similarly, 53 Iranian T1DM patients age 8–18  years and disease duration of less than 8 weeks were all vitamin D deficient (77%) or insufficient (23%) (73). A cross-sectional study of 100 Saudi children with T1DM and 100 healthy controls showed that the mean levels of 25(OH)-Vitamin D (25OHD) were significantly lower in the T1DM children compared to controls (36.7 +/− 14.3 nmol/l versus 44.8 +/− 14.1 nmol/l).…”
Section: Introductionmentioning
confidence: 99%
“…Penilaian asupan vitamin D dari makanan menggunakan kuesioner frekuensi makanan (FFQ) sedangkan besarnya paparan sinar matahari diukur menggunakan kuesioner untuk mengukur jumlah waktu yang dihabiskan anak-anak di bawah sinar matahari dan kebiasaan terkait matahari lainnya. Untuk serum 25(OH)D di uji dengan imunoradiometrik menggunakan kit IDS 41 . Jika ditinjau dari segi karakteristik, penelitian di Iran ini memiliki karakteristik yang paling mirip dengan penelitian yang sekarang dilakukan.…”
Section: Hasil Dan Pembahasanunclassified
“…Hasil penelitian saat ini serupa dengan penelitian cross sectional oleh Ataie-Jafari et al (2012) di Iran dengan karakteristik responden dan metode pengumpulan data asupan kalsium harian yang mirip. Penelitian ini menyatakan bahwa kadar serum 25(OH)D tidak berkorelasi dengan asupan kalsium makanan (p = 0,091) 41 .…”
Section: Hasil Dan Pembahasanunclassified